Da'wah as a Social Process Based on Local Wisdom: A Study of KH. Zainuddin MZ's Figure in the Spread of Moderate Islam in Indonesia - Haerun Nisa; Suprapto; Faizah (al-Afkar, Journal For Islamic Studies, 2026)
The phenomenon of da'wah in Indonesia often faces challenges in maintaining a balance between Islamic values and the socio-cultural realities of a diverse society. The academic issue that arises is how da'wah can function as a social process that not only conveys religious teachings but also builds social awareness and strengthens the values of religious moderation. This study aims to analyze the role of local wisdom-based da'wah through a study of the figure of KH. Zainuddin MZ in spreading moderate Islam in Indonesia. The research method used is a qualitative approach with a case study, through analysis of literature, documentation of lectures, and da'wah messages that are examined thematically. The results of the study show that KH. Zainuddin MZ was able to package da'wah as an effective social process by integrating local values and religious nationalism. His rhetorical, humorous, and contextual communication style made his da'wah messages easily accepted by people from all social strata. This approach shows that da'wah based on local wisdom plays an important role in strengthening the values of tolerance, strengthening social solidarity, and reinforcing the peaceful, moderate, and civilized face of Indonesian Islam.